Peningkatan Hasil Belajar Kesehatan Pribadi Melalui Model Pembelajaran Koperasi Tipe Jigsaw Untuk Siswa Kelas V SD Negeri Telaga Pange - Safianti, Wa Ode; Unmehopa, Wilhelmina (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2024)
Health is the most valuable asset, the expression is said when the person has fallen ill. Healthy at least a person is very dependent on the behavior of the person's daily life. Therefore, everyone needs to be given information about health so that they can lead a life in accordance with health principles. Health aims to improve people's standard of living optimally. In order to achieve this goal, the community is encouraged to know the problems and find ways to overcome the various problems that arise. So far, health development has focused more on efforts to cure diseases, so that the focus of government attention has been directed more towards the development of health facilities such as health centers and hospitals. Soekamto, et al in Titu, (2015) stated the purpose of the learning model is